Handbook of research on global diffusion of broadband data transmission - Dwivedi, Yogesh K.; Papazafeiropoulou, Anastasia; Chaudhuri, Jyoti (Hershey, Pa. : Information Science Reference, 2008)
"This book explores broadband adoption and the digital divide through a global perspective, it provides research on constructs such as relative advantage, utilitarian outcomes, hedonic outcomes, and service quality. From over 100 noted experts in nearly 30 countries, this work allows policy makers, Internet service providers, and others to gain multicultural insight into what factors influence consumers' decisions to adopt boradband" - Provided by publisher
v.1. xlvi, 426, 22 p. - v.2. xlvi, 427-852, 22 p.
Includes bibliographical references and index
Keywords: Internet users -- Attitudes; Digital divide; Internet service providers; Consumer behavior; Broadband communication system; Globalization -- Social aspects